The database POPUM - Demographic database, Umeå university (Umeå University, 2014)
The POPUM database contains personal records from parish registers of the regions Linköping, Sundsvall and Skellefteå, Norrland’s midland and the parishes on the Swedish sides of the cultural region of Sápmi. The database covers parish registers from the end of the 17th century until the end of the 19th century. The personal records stem from different types of parish registers such as catechetical registers, birth and baptism registers, banns and marriage registers, migrations registers, and death registers.

These datasets, ranging from birth to death, provides possibilities to link together individuals and generations. The life stories of individuals as well as family histories can be tracked. Moreover, the dataset offers the possibility to study demographical and socio-economic changes over time across different regions and parishes.

Purpose:

The Demographic Database (DDB) is a special unit at Umeå University with activities focused on two main areas: data production and research. DDB creates and makes available population databases, mainly based on historical information in parish registers during the 18th, 19th, and 20th centuries.

Kyrkoboksdatabasen (även kallad POPUM) innehåller individuppgifter ur kyrkböcker från Linköpings-, Sundsvalls- och Skellefteåregionen, samt Norrlands inland och församlingarna i svenska Sápmi. Databasen omfattar kyrkböcker från slutet av 1600-talet och ända fram till sekelskiftet 1900. De individdata som finns tillgängliga via databasen är baserade på olika typer av kyrkoregister såsom husförhörs- och flyttningslängder, men även födelse- och dopböcker, lysnings- och vigselböcker, samt död- och begravningsböcker.

Genom dessa datamängder, som sträcker sig från födseln till döden, kan man knyta samman både individer och generationer. Detta gör det möjligt att följa individuella livsöden såväl som hela familjers livslopp. Dessutom går det att studera demografiska och socio-ekonomiska förändringar över tid i olika församlingar och regioner.

Med hjälp av DDB:s sökverktyg INDIKO kan du själv fritt söka i kyrkoboksdatabasen. Med verktyget är det bland annat möjligt att återskapa sidor och se direkt in i den digitala källan. För ett datauttag från POPUM krävs en beställning till DDB.

Syfte:

Demografiska databasen (DDB) är en särskild enhet vid Umeå universitet med inriktning på dataproduktion och forskning. DDB skapar och tillgängliggör befolkningsdatabaser, främst baserade på historisk information från kyrkböcker från 1700-, 1800- och 1900-talen.
POPUM - Demografiska databasen
Kyrkoboksdatabasen
Keywords: church; kyrka; baptisms; dop; weddings; bröllop; childbirth; barnafödsel; census data; folkräkningsdata; demography; demografi; demographic statistics; demografisk statistik; emigrants; utvandrare; fertility; fruktsamhet; delivery (pregnancy); förlossning; causes of death; dödsorsaker; vital statistics; befolkningsstatistik; funerals; begravningar; SwedPop; SwedPop; DEMOGRAPHY (POPULATION, VITAL STATISTICS, AND CENSUSES); DEMOGRAFI (POPULATION, VITALSTATISTIK OCH FOLKRÄKNINGAR); Morbidity and mortality; Morbiditet och mortalitet; Censuses; Folkräkningar; Migration; Migration; History and Archaeology; Historia och arkeologi; History; Historia; History of Religions; Religionshistoria